Analisis Tingkat Erosi dan Perencanaan Konservasi Tanah dan Air pada Daerah Aliran Sungai Tukad Oos - Ria, Desak Agung Ade; Trigunasih, Ni Made; Narka, I Wayan; Mega, I Made; Arthagama, I Dewa Made; Soniari, Ni Nengah (Agrotrop : Journal on Agriculture Science, 2025)
Analysis of Erosion Levels and Planning for Soil Water Conservation in the Tukad Oos Watershed. The burgeoning tourism industry in the Tukad Oos watershed has led to the rapid development of supporting facilities such as hotels, villas, and resorts, often perched on steep slopes to showcase breathtaking views. However, this unconventional land use, not aligned with conservation principles, poses a threat of erosion in the Tukad Oos watershed. This study endeavors to assess the extent and distribution of erosion, determine acceptable erosion levels, and propose effective conservation strategies for this picturesque locale. Utilizing field surveys and the Universal Soil Loss Equation (USLE), our findings reveal a wide-ranging erosion rate in the Tukad Oos watershed, spanning from very light to very heavy, with values ranging from 0.11 to 868.50 tons/ha/year. Specific areas, such as land units 1, 8, 9, 10, 11, and 12, exhibit very mild erosion across a combined area of 3,683.17 ha. Moderate erosion is identified in land units 5 and 6, covering 2,821.27 ha, while heavy erosion is evident in land units 2, 3, and 4, comprising 2,935.94 ha. Land unit 7 stands out with very heavy erosion over 772.35 ha. Comparing these findings with the permissible erosion values, ranging from 11.85 to 26.75 tons/ha/year, calls for immediate attention and conservation planning. Our recommended approach involves enhancing vegetation factors through the establishment of mixed gardens with high density. Additionally, land management improvements, focusing on well-constructed terraces, are proposed to mitigate erosion, especially in areas exceeding the allowable limits. This study serves as a vital tool for sustainable development and conservation in the Tukad Oos watershed, ensuring the preservation of its natural beauty amidst rapid tourism growth.